Double-Butter: A Cementation Technique That Significantly Reduces Lipid Contamination of the Tibial Baseplate in Total Knee Arthroplasty - Jacob M. Wilson, MD; Aleksander P. Mika, MD; William W. Gilbert, MD; J. Bohannon Mason, MD; Gregory G. Polkowski, MD; J. Ryan Martin, MD (Arthroplasty Today)
Background: Aseptic loosening is the most common aseptic failure modality following total knee arthroplasty. Recent literature suggests that the implant-cement interface is the “weak-link” in fixation and lipid contamination may drive this debonding pattern. Therefore, the purpose of this study was to determine if the “double-butter” technique would significantly decrease lipid contamination of the tibial tray. Methods: Transparent acrylic models of 7 different tibial baseplates were created to allow for direct visualization of fluid contamination of the implant-cement interface during experimental cementation. Three cementation techniques were then employed in triplicate for each implant: coating only the tibia (“single butter”) and coating of the tibia and baseplate (with and without keel included; “double-butter”). A dye was added centrally to simulate lipid contamination. After each trial, the degree of implant-cement contamination was calculated. Standard statistical analyses were conducted. Results: With the double-butter technique, there was a significant reduction in contamination for all studied implant designs (range: 0%-7%; P < .05) and contamination was eliminated when the entire implant was coated prior to implantation. The single-butter technique resulted in contamination of 16%-43% of the tibial undersurface. There were significant differences in percent contamination between component designs (P < .05). Conclusions: Cementation technique and implant design each influenced baseplate lipid contamination. While significant differences were noted between keel geometries, we found that the double-butter technique effectively eliminated baseplate contamination, even in the most susceptible designs in this study. We therefore advocate for the incorporation of the double-butter technique to limit lipid contamination and potentially reduce aseptic tibial loosening.